Prevalence and susceptibility to diabetes mellitus using Indian diabetic risk score - S., Divya; M. V., Radhamani; Ravi, Kiran; S., Deepa (International Journal Of Community Medicine And Public Health, 2018)
Background: India is the diabetes capital of the world. The burden of diabetes mellitus is increasing daily. If people with higher risk for diabetes are identified before the disease has developed, then some interventions could be undertaken to reduce the modifiable risk factors. Objective of the study was to identify the high risk subjects by using Indian diabetes risk score (IDRS) for detecting undiagnosed diabetes among people aged above twenty five years in rural area of Thrissur. Methods: A cross-sectional study was conducted among 262 inhabitants above 25 in Thrissur. Fasting blood sugar within 3 months prior was noted. The risk of diabetes was assessed using Indian Diabetes Risk Score and grouped into low, moderate and high risk. Results: Majority were females (58.4%) and (80.5%) reported either of their parents as diabetic. Waist circumference was higher for majority. Most (62.2%) people had regular exercise. 199 (76%) had moderate risk. 92% were at moderate to high risk of developing diabetes. Higher the risk score higher was the FBS, and was statistically significant (p=0.035). IDRS was statistically significant with the educational status (p=0.023) and sex (0.000). Forty four (16.8%) were diabetic, 60 (22.9%) hypertensive and 12 (4.6%) had coronary artery disease. Conclusions: There is a shift in age of onset to younger age groups. Hence, the early identification of at risk individuals and appropriate intervention help to prevent, or delay, the onset of complications. This definitely suggests the importance of IDRS for identifying undiagnosed high risk diabetes.